PELATIHAN METODE KERJA ERGONOMI DI PETERNAKAN AYAM UNTUK MENGURANGI RISIKO KELELAHAN KERJA - Bagus Anugrah Ramadhan; Yusuf Nugroho Doyo Yekti; Susmitha Canny (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Occupational fatigue is one of the factors that negatively impacts worker productivity and well-being. Therefore, this community training program aims to increase farmer awareness and knowledge regarding work fatigue management through the application of ergonomics in chicken farming activities. The methods used in this program include field observation, job analysis, and ergonomics training that covers more efficient and safe work techniques. In addition, this program also compares chicken handling, worker health, and work efficiency. The expected results of this activity are increased farmer awareness in implementing more ergonomic work techniques, thereby reducing the risk of injury and work fatigue, as well as increasing the efficiency and well-being of chicken farm workers.